ANALISIS DAERAH RAWAN LONGSOR DAN MITIGASINYA DI KECAMATAN IX KOTO KABUPATEN DHARMASRAYA - Ningrum, Asih Tia; triyatno, triyatno (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
This study aims to 1) analyze the level of landslide susceptibility in District IX Koto, Dharmasraya Regency, 2) to determine the mitigation efforts of landslides in District IX Koto, Dharmasraya Regency. This type of research uses descriptive qualitative methods with data collection techniques in the form of field surveys, field documentation and in the form of report data, as well as other supporting maps. The analysis used is an overlay of parameters that have been determined by scores and weights. The parameters used to analyze the landslide hazard are slope, rainfall, soil type and land use. The results showed that the area with a high level of vulnerability with an area of ​​158.24 Ha or 0,41% of the total area of ​​Kecamatan IX Koto, the area with a moderate level of vulnerability with an area of ​​9,604 Ha or 18,9% of the total area of ​​Kecamatan IX Koto and the area with a low level of vulnerability with an area of ​​40,812 Ha or 80,69% of the total area of ​​Kecamatan IX Koto. There are several stages of disaster mitigation efforts, namely by making terracing in order to reduce the level of steepness of the slopes, evacuating residents whose houses were damaged by landslides and the rehabilitation stage clean up the rest of the destroyed buildings and landslide materials. Keyword : Landslide, Overlay, Landslide Hazard Map, Mitigation